Laparoscopic Adjustable Gastric Banding is a Safe and Effective Treatment for Morbid Obesity - Bakr, Ashraf Aly Mohammad (Society of Laparoendoscopic Surgeons, 1998)
OBJECTIVE: Surgery has been recognized as an effective long-term treatment for morbid obesity. The purpose of this study is to present our experience of laparoscopic adjustable gastric banding (LAGB) as a safe and effective treatment for morbid obesity. METHODS AND PROCEDURES: Over eight months, 39 morbidly obese patients, having a Body Mass Index (BMI) >40 kg/m(2), were included in this study. Conservative measures failed to maintain weight loss in all patients. The procedure is performed through a 5-trocar technique. The procedure involves gastric partitioning and stoma formation by an inflatable band. The stoma can be adjusted by injection of saline in the band reservoir. RESULTS: The mean age of the patients was 31.3 years. The mean BMI was 44.2 Kg/m(2). All procedures were completed laparoscopically. The mean hospital stay was 2.7 days. The morbidity rate was 15.32%. Patients were followed up for a mean period of 6.7 months. The mean BMI after six months (in 28 patients) was 36.6 Kg/m(2). CONCLUSION: Laparoscopic insertion of the adjustable gastric banding is a safe and effective method for the treatment of morbid obesity and should be the standard way of band insertion.